Treatment results of basal-cell carcinoma cases treated at the Hue Central Hospital branch 2 from 2016-2018 - Loi, Nguyen Hong; Phu, Tran Xuan (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
.